An Embedded Software Platform for Distributed Automotive Environment Management. (15th February 2009) - Seepold, Ralf; Martínez Madrid, Natividad; Sáez Gómez-Escalonilla, Jesús; Reina Nieves, Alvaro
Abstract : This paper discusses an innovative extension of the actual vehicle platforms that integrate intelligent environments in order to carry out e-safety tasks improving the driving security. These platforms are dedicated to automotive environments which are characterized by sensor networks deployed along the vehicles. Since this kind of platform infrastructure is hardly extensible and forms a non-scalable process unit, an embedded OSGi-based UPnP platform extension is proposed in this article. Such extension deploys a compatible and scalable uniform environment that allows to manage the vehicle components heterogeneity and to provide plug and play support, being compatible with all kind of devices and sensors located in a car network. Furthermore, such extension allows to autoregister any kind of external devices, wherever they are located, providing the in-vehicle system with additional services and data supplied by them. This extension also supports service provisioning and connections to external and remote network services using SIP technology.